GUGATAN PEMBATALAN MEREK TERDAFTAR OLEH PEMILIK MEREK TERKENAL ( Studi Kasus: Putusan MA No. 402 K/Pdt .Sus/2011). - Haris Fadhilah Putra; T. Keizerina Devi Azwar; Windha windha (Universitas Sumatera Utara, 2013)
Brand is very important in the business world. Brand products (both goods and services) that are certain to be popular and sell well in the market of course would tend to make spur other manufacturers or entrepreneurs competing products with famous brand, even in this case finally appeared unfair competition. Brands used in the trade, which in turn may submit the national economy. Pemdaftaran brand basically meant that the mark is used in commerce. The issue in this thesis is how the system of trademark registration in Indonesia, how to register for the legal protection of well-known brand in Indonesia, as well as how the lawsuit registered trademark by the owner of the famous brands in Indonesia. Methods of research using this type of normative legal research. Source of data used are secondary data, which consists of primary legal materials, secondary, and tertiary. Data was collected with library research techniques and data analysis using inductive qualitative approach and dedukatif. Mark registration system in Indonesia is currently contained in that set in Trademark Law No. 15 of 2001 is a constitutive system but before Indonesia also familiar with declarative system adopted in the Brand Law No. 15 of 2001. The meaning is constitutive sitem party has registered its brand, it creates a registration rights to the trademark, registered parties he was the only one who has the right to a brand and third-party registrar must respect his rights as an absolute right. Registration of the trademark protection law known governed exclusively However the brands that have been registered are allowed to be given an explanation and how to brand holders may submit the registration against any other brand. Kata kunci: Gugatan pembatalan, Merek, Merek terkenal